Pemahaman peraturan permainan tenis lapangan pada peserta penataran wasit tenis lisensi daerah Riau 2018 - Jatra, Rices; Fernando, Debi Dori (Universitas Nusantara PGRI Kediri, 2019)
Tennis is a very popular sport and has become worldwide. It is very necessary for an umpire or officer to lead a match. One of the tennis game officers is a chair umpire who led the match directly to the court. Tennis matches in Riau had started a lot. The number of matches in Riau had to be supported by professional umpires. To become a professional umpire certainly must be supported by mastering the rules of the tennis game properly. This research was a descriptive study by giving a test to the participants of the umpire training who had participated in upgrading activities to determine the level of tennis game rules understanding. The sample of this study was participants who had participated in the court tennis umpire training. The research sample was 25 (twenty five) people. The study was located in Bangkinang, Kampar District on January 6, 2019. The results showed that the level of court tennis game rules understanding with very good category was 8%, good category was 12%, medium category was 56%, less category was 16%, while very less category was 8% . These results could provide a conclusion that the level of court tennis game rules understanding of the training participants was in the medium category.